Neutropenia, agranulocytosis and dipyrone - Hamerschlak, Nelson; Cavalcanti, Alexandre Biasi (São Paulo Medical Journal, 2005)
CONTEXT: Neutropenia and agranulocytosis may be defined as granulocyte counts of less than 1,500/mm3 and 500/mm3, respectively. Agranulocytosis is a rare and serious disease often caused by drugs. Its mortality rate is around 10%. The most common manifestations are infections such as tonsillitis, pharyngitis, stomatitis or pneumonia. Although dipyrone is one of the drugs known to be associated with agranulocytosis, the strength of the association has been a matter of much debate. Moreover, alternative analgesic and antipyretic agents are not devoid of serious side effects. CONCLUSIONS: It is therefore necessary to establish the incidence of agranulocytosis in Latin America and the role of dipyrone. The on- going LATIN Study is a multicenter international case-control study that will provide answers for these questions.